2018
DOI: 10.1002/ccr3.1693
|View full text |Cite
|
Sign up to set email alerts
|

A novel FBN2 mutation cosegregates with congenital contractural arachnodactyly in a five‐generation Chinese family

Abstract: Key Clinical MessageWe identified a novel heterozygous mutation (c.4177T>G and p.Cys1393Gly) in FBN2 that cosegregated with congenital contractural arachnodactyly (CCA) in a five‐generation Chinese family. This mutation may cause the loss of the disulfide bond between Cys 1393 and Cys 1378 residues of fibrillin‐2. Our study expands the genetic profile of CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Fibrillins-2 is one of the glycoprotein components incorporated extracellularly on microfibrils and is essential in bone, muscle, and extracellular matrix formation [63]. It is well known that mutation of FBN2 leads to dominant heritable connective tissue disorders [64]. Importantly, a recent review article has gained insight on fibrillin-2 as a critical mediator that binds to transforming growth factor-beta (TGF-β) during extracellular matrix formation [65].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillins-2 is one of the glycoprotein components incorporated extracellularly on microfibrils and is essential in bone, muscle, and extracellular matrix formation [63]. It is well known that mutation of FBN2 leads to dominant heritable connective tissue disorders [64]. Importantly, a recent review article has gained insight on fibrillin-2 as a critical mediator that binds to transforming growth factor-beta (TGF-β) during extracellular matrix formation [65].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillins-2 is one of the glycoprotein components incorporated extracellularly on micro brils and is essential in bone, muscle, and extracellular matrix formation [61]. It is well known that mutation of FBN2 leads to dominant heritable connective tissue disorders [62]. Importantly, a recent review article has gained insight on brillin-2 as a critical mediator that binds to transforming growth factor-beta (TGF-β) during extracellular matrix formation [63].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of both genes leads to Musculo-skeleton tissue disorders, which are typical features in the SLE [58]. Recently, studies in Chinese and Turkish SLE patients found the mutation of FBN2 was a marker for congenital contractural arachnoldactyly (CCA) or Beals syndrome, a rare autosomal dominant congenital connective tissue disorder [57,59,60]. Although none of the evidence has been identi ed FBN2 as SLE susceptible allele, pristane induced spontaneous LN developed mouse model (SWR X NZB1 F1) demonstrated the upregulation of FBN2 correlated with brosis prevalence [61].…”
Section: Discussionmentioning
confidence: 99%